Anterior Versus Posterior Decompression for Degenerative Thoracic Spine Diseases: A Comparison of Complications. Issue 4 (May 2021) - Abedi, Aidin; Formanek, Blake; Hah, Raymond; Buser, Zorica; Wang, Jeffrey C.
Study Design: Retrospective database. Objectives: Although posterior decompression is the most common approach for surgical treatment of degenerative thoracic spine disease, anterior approach is gaining interest due to its advantage in disc visualization. The objective of this study was to compare the intra- and postoperative medical complication rates between anterior and posterior decompression for degenerative thoracic spine pathologies. Methods: A national US insurance database was queried for patients with degenerative diagnoses who had undergone anterior or posterior thoracic decompression. Incidence of intra- and postoperative complications were evaluated on the day of surgery and within 1 and 3 months. Two subgroups were matched based on age, gender, and comorbidity. The association of decompression approach and complications was assessed using logistic regression. Results: A total of 1459 patients were included, consisting of 1004 patients in posterior and 455 patients in anterior group. Respiratory complications were the most common complications on the day of surgery (8.57%) and within 30 days (17.75%). Matched analysis showed that anterior approach was associated with organ failure, gastrointestinal, and device-/implant-/graft-related complications in all follow-up periods; and with cardiovascular, deep venous thrombosis/pulmonary embolism, and respiratory complications in at least 1 follow-up period. Among respiratory complications, anterior decompression was significantly associated with noninfectious etiologies on the day of surgery (odds ratio [OR] = 1.72), within 30 days (OR = 2.05), and within 90 days (OR = 1.92). Conclusions: Anterior approach was associated with increased rates of several complications. High rates of respiratory complications necessitate comprehensive preoperative risk stratification to identify those who may benefit more from posterior approach.